COLOR REMOVAL OF TREATED TEXTILE WASTEWATER AS RECLAIMED WATER USING OZONATION - Ima Wantoputri, Noviani
The textile industry is one of industries that growing rapidly in Bandung, Indonesia which discharge enormous quantity of highly colored wastewater and can make pollution. Beside pollution, many textile industries still use groundwater in their production process that cause groundwater surface and land subsidence. From those problems, there is potency to recycle textile wastewtaer as reclaimed water for textile production process. But, one of the problems in processing textile wastewater with conventional treatment method is the ineffectiveness of color removal. A further treatment as post treatment is needed for treated wastewater discharge to remove the color. One of the methode is by using ozonation method. In this study, the decolorization of artificial textile wastewater containing azo dye reactive-black 5 (RB5) from secondary treatment was investigated in batch and continuous system. Artificial treated textile wastewater from secondary biological treatment was made using 5 mg/L azo dye RB5 in 16 L volume of reactor. The preliminary batch study showed that the optimum color removal achieved in 24.66 mg/minute ozone dose in batch system with 39,17 mg/L ozone consumption. Within 2 minutes of ozonation, color removal achieved 75,57% and achieved 100% in 10 minutes. In 30 minutes ozonation, COD removal achieved 75%. The kinetics of the reaction rate in this batch ozonation followed pseudo first order reaction. Continuous system operation conducted with up flow influent feeding using variation of color concentration (5, 10 and 15 mg/L) and also variation of HRT (5,10 and15 minutes). The experiments showed that the longer HRT tends to have higher color removal efficiency with its residual ozon was also higher. The optimum variation with the highest color removal was in 5 mg/L dye concentration and 15 minutes of HRT. The color, COD, amonia, TSS, oil and grease removal were 81%; 75%; 28,57%; 39,02% and 68,54% respectively. The color rate kinetic, ozone coefficient transfer ((KL?O3) and ozone consumption per liter wastewater were 0,869/ minute; 0,005/minute, dan 12,64 mg/L respectively. From this study, the ozonated effluent were potencial to be used as reaclaimed water.